Recursos argumentativos presentes em textos dos gêneros ensaio e artigo de opinião: uma abordagem sistêmico-funcional - Marchetti, Greta Nascimento (2015)
This research aimed to analyse structural and rethorical features of an essay and an opinion piece, both published in wide national range newspaper and magazine. The acts of telling and describing a story or a happening are configured as linguistic operations performed by an individual since early ages, which results in an event reconstruction or in capturing an own experience moment. When arguing, commenting or positioning about a topic, someone passes judgement on the subject under discussion to persuade the listener. This requires knowledge of the subject that will address and a critical position taken hereafter it. Recent studies have shown that children as young as 4 or 5 years old dominate the oral dissertation discursive form already well developed, which gives them a satisfactory communication, although far from written language formal lines. However, dissertative-argumentative texts are often teaching objects, specifically in the final years of elementary school and high school, aiming to build an academic and scientific speech, known as a product of student education process, within the formal bases. Thus, given the complexity involving the action of arguing and the construction of an argumentative written speech, this study focuses on essay and opinion piece genres, in addition to examining argumentation issues, involving genre structure, as well as assessment resources, in view of persuading that is inherent in arguments. The research, which presents a critical nature, with the support of Functional Systemic Grammar, aims to answer the following questions: (a) How is characterized the structure of the essays and opinion pieces which were analyzed? (b) How is the argument built in these texts? (c) Which persuasive resources are used in argumentative process?